Bethe ansatz solutions for temperley-lieb quantum spin chains - Ghiotto, R. C.T. [UNESP]; Malvezzi, A. L. [UNESP] (World Scientific Publishing, 2000)
We solve the spectrum of quantum spin chains based on representations of the Temperley-Lieb algebra associated with the quantum groups U(q)(X(n)) for X(n) = A1, B(n), C(n) and D(n). The tool is a modified version of the coordinate Bethe ansatz through a suitable choice of the Bethe states which give to all models the same status relative to their diagonalization. All these models have equivalent spectra up to degeneracies and the spectra of the lower-dimensional representations are contained in the higher-dimensional ones. Periodic boundary conditions, free boundary conditions and closed nonlocal boundary conditions are considered. Periodic boundary conditions, unlike free boundary conditions, break quantum group invariance. For closed nonlocal cases the models are quantum group invariant as well as periodic in a certain sense.